Robotic vs. minimally invasive mitral valve repair: A 5‐year comparison of surgical outcomes. Issue 10 (21st August 2022) - Zheng, Clark R.; Mazur, Piotr; Arghami, Arman; Jahanian, Sepideh; Viehman, Jason K.; King, Katherine S.; Dearani, Joseph A.; Daly, Richard C.; Rowse, Phillip G.; Bagameri, Gabor; Crestanello, Juan A.
Abstract: Background: Minimally invasive mitral valve repair (MVr) is commonly performed. Data on the outcomes of robotic MVr versus nonrobotic minimally invasive MVr are lacking. We sought to compare the short‐term and mid‐term outcomes of robotic and nonrobotic MVr. Methods: We reviewed all patients who underwent robotic MVr ( n = 424) or nonrobotic MVr via right mini‐thoracotomy ( n = 86) at Mayo Clinic, Rochester, MN, from January 2015 to February 2020. Data on baseline and operative characteristics, operative and long‐term outcomes were analyzed. Patients were matched 1:1 using propensity scores. Results: Sixty‐nine matched pairs were included in the study. The median age was 59 years (interquartile range [IQR]: 54–69) and 75% ( n = 103) were male. Baseline characteristics were similar after matching. Robotic and nonrobotic MVr had similar operative characteristics, except that robotic had longer cross‐clamp times (57 [48–67] vs. 47 [37–58] min, p < .001) and more P2 resections (83% vs. 68%, p = .05) compared to nonrobotic MVr. There was no difference in operative outcomes between groups. Hospital stay was shorter after robotic MVr (4 [3–4] vs. 4 [4–6] days, p = .003). After a median follow‐up of 3.3 years (IQR, 2.1–4.5), there was no mortality in either group, and there was no difference in freedom from mitral valve reoperations between robotic and nonrobotic MVr (5 years: 97.1% vs. 95.7%, p = .63). Follow‐up echocardiogram analysis predicted excellent freedom from recurrent moderate‐or‐severe mitral regurgitation at 3 years after robotic and nonrobotic MVr (90% vs. 92%, p = .18, respectively). Conclusions: Both short‐term and mid‐term outcomes of robotic and nonrobotic minimally invasive mitral repair surgery are comparable.